The relationship between memorable experience, travel satisfaction, and tourist expectations on revisit intention among tourists in malaysia - Lim Xin Min; Low Jun Xuan; Luqman Nur Hakim Rahmat; Maisarah Ghzali (2023)
This research aims to examine the relationship between memorable experiences, travel satisfaction, and tourist expectations on revisit intention among tourists in Malaysia. It is discovered memorable experiences, travel satisfaction, and tourist expectations were the major reason that affected tourists’ revisit back to a destination. Tourists around Malaysia were targeted respondents, and 200 respondents successfully responded through the online survey. Data collected was analyzed by using Statistical Package for Social Science (SPSS) version 29.0. SPSS Statistical addresses the entire statistical analysis process such as planning, data collection, analysis, and reporting for better decision-making and performance. The Pearson correlation coefficient was used in this research to investigate the relationship between memorable experiences, travel satisfaction, and tourist expectations toward revisit intention. The result shows a significant effect of memorable experiences, travel satisfaction, and tourist expectations toward revisit intention. Through this study can understand that most tourists will revisit a destination for different reasons. Keywords: Revisit intention, memorable experiences, travel satisfaction, tourist expectation, tourist